Análise diagnóstica para implantação de serviços de farmácia clínica em um hospital público de alta complexidade - Alcântara, Thaciana dos Santos (2016)
In hospitals, when the pharmaceutical incorporates in your routine the clinical practice, several barriers and facilitators influencing the establishment of Clinical Pharmacy Services. One of the criteria that favor the successful implementation of innovative practices is to understand the perceptions of professionals involved in the practice as well as environmental analysis and qualification of these professionals. Objectives: Understand the perception of a group of pharmacists and key informants on the implementation of clinical pharmacy services in a public hospital of high complexity; analyze the structure (physical and pharmaceutical communication abilities) exists for the development of Clinical Pharmacy services in this institution. Methodology: The first stage corresponds to a qualitative study, which was conducted a focus group with 16 pharmaceutical and interviews with professional managers of pharmaceutical classes (2), nursing (1) and health (1). The data analysis was performed by the content analysis technique. In the second stage was carried the evaluation of the structure to the provision of clinical pharmacy services at the hospital. To analyze the physical structure was used an instrument elaborated based on the ordinance 4,283 / 10 from the Ministry of Health and the Canadian accreditation quality indicators. The pharmaceutical communication abilities were evaluated using the adapted instrument "Assessment of pharmaceutical care process." Results: Stage 1- The perception of pharmacists and other professionals brought topics such as the outdating of the pharmaceutical profession, the resistance of some professionals and difficulties in communicating the multidisciplinary team. Also listed were facilitators for the service and the experience of some professionals in the Clinical Pharmacy services as well as the expectations were related to the improvement in the rational drug use process. Stage 2 - The evaluation of the physical structure was considered inadequate for Clinical Pharmacy services in most of the items evaluated. Inadequacies were found in the location of pharmacies in the hospital and private environment to the pharmaceutical care service, as well as in normative and organizational instruments of pharmacies. In relation to communication abilities, the overall impression of the pharmacist's responsibilities to the Clinical Pharmacy Services was considered regular (3) on a scale of 1-5 the instrument used. Conclusion: The analysis of the perception of participants allow the knowledge of factors such as barriers and facilitators that may influence the implementation of Clinical Pharmacy Services. In the evaluation of the structure important indicators for the development of pharmaceutical services were considered non-conforming to the instrument, which can hamper the clinical practice of pharmacists. Regarding pharmaceutical communication skills, the results indicate difficulties of interaction with the patient as well as other professionals. In this perspective, these results can guide planning for implementation of Clinical Pharmacy in hospitals.